1989
DOI: 10.1016/0014-5793(89)81087-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein kinase C induces differentiation of neuroblastoma cells

Abstract: It is shown that 1-(5-isoquinolinylsulfonyl)-2-methylpiperazine (H7), a specific inhibitor of protein kinase C, induces neuritogenesis in neuro 2a cells. The percentage of differentiated cells was 9%, 20%, 59% and 85% at 0, 17, 85 and 500 ~tM H7, respectively. The number of neurites/cell increased 2-, 8-and 14-fold over the controls for 17, 85 and 500 gM H7, respectively. These results indicate that protein kinase C plays a key role in the control of differentiation of neural cells and that its specific inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…In fact, inhibition of DNA synthesis in neuroblastoma cells causes a rapid depletion of PKC (Minana et al, 1989), which is in agreement with our observation of neurite outgrowth following PKC inhibition.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In fact, inhibition of DNA synthesis in neuroblastoma cells causes a rapid depletion of PKC (Minana et al, 1989), which is in agreement with our observation of neurite outgrowth following PKC inhibition.…”
Section: Discussionsupporting
confidence: 89%
“…The cyclic AMP-dependent protein kinase, protein kinase A (PKA) and the Ca2 + , phospholipid-dependent protein kinase, protein kinase C (PKC), are highly expressed in nervous tissue (for review, see Nestler and Greengard, 1984) and function in neuronal differentiation, neuritogenesis, cytoskeletal protein phosphorylation, long-term potentiation, and neuronal circuit cytoarchitecture (Aletta et al, 1989;Clark and Lee, 1991;Felipo et al, 1990;Hammerling et al, 1987;Heikkila et al, 1989;. , 1987; Leli et al, 1991;Mattson, 1990;Minana et a]., 1989;Olds et al, 1989;Sihag et al, 1988). Furthermore, neurite extention by many neuronal cell lines following treatment with the cAMP analogue dbcAMP (Abraham et al, 1991;Prasad and Hsie, 1971;Shea et al, 1985) is likely to be due to PKA activation, since dbcAMP, like CAMP, functions solely through PKA activation (Adelstein, 1982;Glass and Krebs, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Protein kinase C plays a pivotal role in neuronal differentiation and homeostasis. Inhibition of protein kinase C (PKC) promotes neurite outgrowth, whereas activation restricts it (Minana et al, 1989;Tsuda et al, 1989;Heikkila et al, 1991;Shea and Beermann, 1991;Ono et al, 1991Ono et al, , 1993Leli et al, 1992a,b;Shea et al, 1992a). Two modes of PKC activation have been described.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a decline in PKC and/or continuous activation of PKA is also involved in neurite formation, particularly in neurite maintenance. It has been reported that a PKC inhibitor, l-(5-isoquinolinylsulfonyl)-2-methylpiperazine (H-7), induces neurite elongation in mouse neuroblastoma Neuro 2a cells (Minana et al, 1989), N18TG-2 cells (Tsuda et al, 1989), or human neuroblastoma cells (Parodi et al, 1990). In human neuroblastoma LA-N-5 cells, dephosphorylation of 80-kDa PKC substrate by a decline in PKC activity also correlates to neurite extension (Girard and Kuo, 1990).…”
Section: Discussionmentioning
confidence: 99%